9514 1404 393
Answer:
a) y' = x^2(3x·ln(6x) +1)
b) y' = 6e^(3x)/(1 -e^(3x))^2
Explanation:
The applicable rules for derivatives include ...
d(u^n)/dx = n·u^(n-1)·du/dx
d(uv)/dx = (du/dx)v +u(dv/dx)
d(e^u)/dx = e^u·du/dx
d(ln(u))/dx = 1/u·du/dx
__
(a)
![y=x^3ln((6x))\\\\y'=3x^2ln((6x))+(x^3\cdot6)/(6x)\\\\\boxed{(dy)/(dx)=3x^3ln((6x))+x^2}](https://img.qammunity.org/2021/formulas/mathematics/high-school/eltk16glf4p7gvhwn91sccr5cu348caakl.png)
__
(b)
![y=(1+e^(3x))/(1-e^(3x))=1+(2)/(1-e^(3x))=1+2(1-e^(3x))^(-1)\\\\y'=-2(1-e^(3x))^(-2) (-3e^(3x))\\\\\boxed{(dy)/(dx)=(6e^(3x))/((1-e^(3x))^2)}](https://img.qammunity.org/2021/formulas/mathematics/high-school/7fccdhqv2wugw84h9efq4jh4ta9z422u56.png)